Editorial on the article entitled “brigatinib efficacy and safety in patients with anaplastic lymphoma kinase (ALK)-positive nonsmall cell lung cancer in a phase I/II trial” - Sullivan, Ivana; Planchard, David (Journal of Thoracic Disease, 2016)
Anaplastic lymphoma kinase (ALK)-rearrangements occur in 3–7% of patients with non-small cell lung cancer (NSCLC) and are more common among patients with a never/light smoking history, adenocarcinoma histology, youngers and in tumors wild-type for EGFR and KRAS genes (1-4). Crizotinib (Xalkori®; PF-02341066; Pfizer), a small molecule inhibitor of ALK, ROS1 and MET (5-7), was the first tyrosine kinase inhibitor (TKI) approved by the Food and Drug Administration (FDA) and the European Medicine Agency (EMA) for patients with NSCLC who have the ALK gene rearrangement, because it induces rapid tumor regression and objective responses around 70% in the majority of such patients, both in first and second line settings (8,9).